Eribulin for the treatment of advanced breast cancer: A prospective observational registry study. (6th November 2022) - Kenny, Laura; Beresford, Mark; Brown, Ian; Misra, Vivek; Kristeleit, Hartmut
Abstract: Objective: Eribulin treatment improved overall survival with predictable toxicities in phase 3 trials of patients with previously treated, locally advanced/metastatic breast cancer. This study (NCT02443428) prospectively observed eribulin‐treated patients in real‐world clinical practice. Methods: This observational multicentre registry study enrolled 76 patients with locally advanced/metastatic breast cancer who had ≤2 prior chemotherapeutic regimens for advanced disease. Eribulin was administered at a 1.23 mg/m 2 dose (days 1 and 8 of every 21‐day cycle). Adverse events (AEs) were monitored and effectiveness was assessed per local practice. Results: AEs occurred in 98.7% of patients; 88.2% had eribulin‐related AEs. The most common AEs were fatigue (64.5%), alopecia (36.8%), nausea (35.5%) and constipation (30.3%). Serious AEs occurred in 42.1% of patients. The most common grade 3/4 AEs were neutropenia (9.2%), febrile neutropenia (9.2%), dyspnoea (5.3%) and pleural effusion (5.3%). No fatal AEs occurred. Dose reductions occurred in 31.6% of patients, 42.1% experienced dose delays and 9.2% discontinued due to worsening condition. There were complete responses in 2.6% and partial responses in 15.8% of patients. Median time to progression and overall survival were 4.0 and 8.3 months, respectively. Conclusion: Eribulin was well tolerated in real‐world clinical practice, comparable to safety and effectiveness reported in other clinical trials.